The Relationship between Automobile Liability Costs and Government Social Spending - Kleffner, Anne E.; Born, Patricia; Chan, David (Assurances et gestion des risques / Insurance and Risk Management, 2010)
Liability insurance is one of the primary mechanisms for compensating individuals who are injured in auto accidents. An injured individual’s propensity to seek compensation through the legal system depends on his or her expected payoff and access to other sources of compensation. A justification for social insurance programs that provide compensation to injured parties is the potential for such compensation to reduce the need for victims to seek compensation through the legal system. If such programs serve as substitutes for the legal system as sources of compensation, then we expect that as spending on these programs decreases, liability costs will increase, and vice-versa. Using State-level data for the U.S., and provincial-level data for Canada, we evaluate the relationship between government health/welfare spending and automobile liability insurance costs. Our results suggest a small but significant substitute relationship in both countries. Information that substantiates a connection between these sources will be useful in public assistance decision-making.